EXERCISE, BLOOD PRESSURE AND MORTALITY: FINDINGS OF EIGHT YEARS OF FOLLOW-UP - Turi, Bruna Camilo [UNESP]; Bonfim, Mariana Rotta [UNESP]; Codogno, Jamile Sanches [UNESP]; Fernandes, Romulo Araujo [UNESP]; Muniz de Araujo, Lia Grego [UNESP]; Amaral, Sandra Lia do [UNESP]; Monteiro, Henrique Luiz [UNESP] (Soc Brasileira Med Esporte, 2017)
Introduction: In the last decades, unhealthy habits, such as low levels of physical activity and poor diet, have increased. Consequently, the prevalence of cardiovascular diseases and mortality has increased significantly among adults. However, it is known that regular physical exercises help to improve health outcomes. Thus, the aim of this study was to analyze the effects of eight years of regular participation in an exercise program on blood pressure and mortality in the Brazilian public health system. Methods: The sample consisted of 34 participants with hypertension and/or type II diabetes who were followed up for eight years. They were paired by age, body mass index and chronic disease in two groups: exercise and control. During the follow-up period, medical records were used to assess systolic and diastolic blood pressure, as well as number of medical appointments and the occurrence of deaths. Results: In the follow-up period, five participants died in the control group and none in the exercise group. The Kaplan-Meier analysis identified 29.4% lower mortality among active participants (Fisher's exact test with p = 0.044). The number of medical appointments and the values of diastolic blood pressure were significantly lower for active participants. Conclusion: After a follow-up of eight years, participants in the exercise group attended fewer medical appointments, had better blood pressure control and a lower occurrence of deaths.
Keywords: mortality; hypertension; diabetes mellitus; exercise